Covid-19 Memudarkan Rasa Kemanusiaan Terhadap Sesama Dan Implikasinya Bagi Orang Percaya - Simon Simon; Lindin Anderson (Sekolah Tinggi Teologi Nusantara, 2020)
ABSTRACTThis paper highlights the fading sense of humanity towards others due to the influence of Covid-19. The understanding of humanity as referred to in this paper, of course, departs from a Christian theological perspective. The meaning of humanity means empathy or concern in understanding the difficulties experienced by others, as well as being an active actor in overcoming the burdens of other people's lives without seeking profit. The method used in this paper is descriptive qualitative with a phenomenological approach. The results of this discussion obtained an explanation, that government policies in dealing with Covid-19 are sometimes not pro-people. Then those who were expose to Covid-19, received negative stereo types from others, then there were hospitals that took advantage of Covid-19 victims for an incentive. Paramedic services are not optimal for some patients, and there are still people who do not fully comply with health protocols. In a climate of social conditions that have begun to diminish the sense of humanity, it is fitting for believers (Christians) to become light and salt by practicing the universal truth of God's word through their deeds to others.ABSTRAKTulisan ini menyoroti mulai memudarnya rasa kemanusiaan terhadap sesama karena pengaruh Covid-19. Pengertian rasa kemanusiaan yang dimaksud dalam tulisan ini tentunya berangkat dari perspektif teologis Kristen. Adapun makna kemanusiaan yang dimaksud adanya empati atau kepedulian dalam memahami kesulitan yang dialami oleh orang lain, serta menjadi pelaku aktif dalam menanggulangi beban hidup orang lain tanpa mencari keuntungan. Metode yang dipakai dalam tulisan ini menggunakan kualitatif deskriptif dengan pendekatan fenomologis. Hasil dari pembahasan ini didapatkan suatu pemaparan, kebijakan pemerintah dalam penanggulangan Covid-19 terkadang tidak bersifat pro ke-rakyat. Kemudian mereka yang terpapar Covid-19, menerima streo type negatif dari sesama, kemudian adanya rumah sakit yang mengambil keuntungan dari korban Covid-19 demi sebuah insentif. Pelayanan tenaga medis yang tidak maksimal ke-sebagian pasien, serta masih dijumpainya masyarakat yang tidak sepenuhnya patuh pada protokol kesehatan. Iklim kondisi sosial yang mulai memudarkan rasa kemanusiaan, sudah sepatutunya orang percaya (Kristen) menjadi terang dan garam dengan mengamalkan kebenaran firman Allah secara menguniversal melalui perbuatannya kepada sesama.